2022
DOI: 10.1080/19490976.2022.2121580
|View full text |Cite
|
Sign up to set email alerts
|

Limosilactobacillus reuteri DS0384 promotes intestinal epithelial maturation via the postbiotic effect in human intestinal organoids and infant mice

Abstract: Little is known about the modulatory capacity of the microbiota in early intestinal development. We examined various intestinal models that respond to gut microbial metabolites based on human pluripotent stem cell-derived human intestinal organoids (hIOs): physiologically relevant in vitro fetal-like intestine, intestinal stem cell, and intestinal disease models. We found that a newly isolated Limosilactobacillus reuteri strain DS0384 accelerated maturation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…In this study, we detected that the postbiotics enhance intestinal epithelial wound healing after a mechanical injury such as a cell scratch in IPEC-J2 cells. It was also reported by Lee et al ( 2022 ) that the postbiotics of L. reuteri DS0384, prepared with liquid fermentation, promoted intestinal stem cell proliferation and protected intestinal epithelial cells from cytokine-induced injury. These findings indicated that postbiotics played a crucial role in health and nutrition.…”
Section: Discussionmentioning
confidence: 62%
“…In this study, we detected that the postbiotics enhance intestinal epithelial wound healing after a mechanical injury such as a cell scratch in IPEC-J2 cells. It was also reported by Lee et al ( 2022 ) that the postbiotics of L. reuteri DS0384, prepared with liquid fermentation, promoted intestinal stem cell proliferation and protected intestinal epithelial cells from cytokine-induced injury. These findings indicated that postbiotics played a crucial role in health and nutrition.…”
Section: Discussionmentioning
confidence: 62%
“…Among these bacteria, L. reuteri stands out due to its ability to produce various bene cial metabolites vital for bodily functions and its profound impact on the microbial community structure 32,33 . Previously studies have shown that L. reuteri can effectively enhance gut and central nervous system development in offspring whose mothers were exposed to high-fat diet, LPS, or antibiotic 34,35 . In our multi-omics analysis, L. reuteri emerged as a key species contributing to ENS development.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal mucus acts as a barrier to protect the intestinal epithelial cells from harmful substances and is crucial for maintaining good health [1]. A growing body of evidence confirms that LAB promote intestinal mucin secretion and strengthen the intestinal mucus barrier [13][14][38][39] . Herein, we found that L. acidophilus FCQHC4L1 strengthened the intestinal mucus barrier.…”
Section: Discussionmentioning
confidence: 99%